2018
DOI: 10.1155/2018/8981561
|View full text |Cite
|
Sign up to set email alerts
|

Use of Awake Flexible Fiberoptic Bronchoscopic Nasal Intubation in Secure Airway Management for Reconstructive Surgery in a Pediatric Patient with Burn Contracture of the Neck

Abstract: Although the use of awake flexible fiberoptic bronchoscopic (FFB) intubation is a well-recognized airway management technique in patients with difficult airway, its use in smaller children with burn contractures or in an uncooperative older child may be challenging. Herein, we report successful management of difficult airway in a 7-year-old boy with burn contracture of the neck, by application of FFB nasal intubation in a stepwise approach, first during an initial preoperative trial phase to increase patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For the anticipated difficult airway awake fiberoptic intubation is still the gold standard [21]. In awake patients, fibreoptic intubation is easier as the tongue does not fall back in the pharynx, and spontaneous ventilation keeps the airway open.…”
Section: Discussionmentioning
confidence: 99%
“…For the anticipated difficult airway awake fiberoptic intubation is still the gold standard [21]. In awake patients, fibreoptic intubation is easier as the tongue does not fall back in the pharynx, and spontaneous ventilation keeps the airway open.…”
Section: Discussionmentioning
confidence: 99%
“…However, Totoz and Tolga et al reported that a patient with restricted mouth opening and fixed flexion deformity needs to be intubated in a fully awake condition and that a preoperative demonstration and explanation are important in a successful procedure. 3 Sharma et al used asleep fiberoptic intubation with an incremental dose of sevoflurane with maintenance of spontaneous breathing in a child with limited mouth opening for temporomandibular joint ankylosis. 4 In a child with giant hemangioma of the tongue, Mazlan et al used a combination of a loading dose and infusion of dexmedetomidine and a titrating dose of midazolam and fentanyl to allow smooth and successful intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Although a nasal approach is more tolerable in a pediatric patient, a randomized comparative study by Chahar et al found fewer alterations in hemodynamic profiles and a faster intubation time in oral intubation. 3,10 In a patient with base of the skull or panfacial fracture, although nasal intubation was not totally contraindicated and reducing surgical airway, the procedure might predispose a risk toward intracranial intubation without fiberoptic guide. 11,12 As our patient required nasal intubation, a combination of lignocaine nebulization, nasal packing with cocaine, topical lignocaine in the nasopharyngeal tube, lignocaine spray on the tonsillar pillar and posterior pharynx and the 'spray as you go' technique during fiberoptic intubation ensured adequate analgesia to the upper airway.…”
Section: Discussionmentioning
confidence: 99%
“…These range from simple instruments like a laryngeal mask airway to more advanced skills like fibreoptic intubation [8]. A case report in 2018 successfully demonstrated use of fibreoptic bronchoscopy for intubation in pediatric burn patients [9].…”
Section: Discussionmentioning
confidence: 99%